Challenges in the Adoption of International Public Sector Accounting Standards
XVII, 134 p.
Keywords: The aim of this book is to take stock of the experiences of Spain and Portugal in the adaptation to the IPSASs, showing the advantages, disadvantages and the main challenges for its implementation. In chapter one, the book analyses the IPSAS and the conceptual framework, as well as the claimed benefits and criticisms of IPSAS. Chapter two makes an analysis of the diffusion of the IPSAS in the international framework and the process of harmonization in development in Europe. Chapter three and four analyze the process of adaptation to IPSAS in Portugal and Spain respectively. In the chapter five, there is a comparative analysis between Spain and Portugal, and the last chapter presents the main conclusions. This book can help to understand the level of implementation of the reforms and how governments are applying the IPSAS. Isabel Brusca is Professor of Accounting and Finance at the University of Zaragoza, Spain, and a certified public accountant. Patrícia Gomes is Professor of Accounting in the Department of Accounting and Taxation at the Management School of the Polytechnic Institute of Cávado and Ave, Barcelos, Portugal, and a research member of the Research Center on Accounting and Taxation. Maria José Fernandes is Professor of Accounting in the Department of Accounting and Taxation at the Management School of the Polytechnic Institute of Cávado and Ave, Barcelos, Portugal. She is also President of the Polytechnic Institute of Cávado and Ave. Vicente Montesinos is Emeritus Professor of Accounting and Finance at the University of Valencia, Spain, and a Registered Chartered Accountant. He has been Dean of his Faculty and President of the Spanish Academic Accounting Association.